ROSJA W UKRAIŃSKICH MEMACH INTERNETOWYCH (OKRES WOJENNY 2022-2023) - Pociechina, Helena (Przegląd Wschodnioeuropejski, 2024)
This paper contains a linguistic analysis of visual messages published on the Internet (mainly on Ukrainian websites) in the period from the beginning of Russia’s full-scale invasion of Ukraine on February 24, 2022 to mid-2023. The content of the messages reflects current war events in the form of comments satirical, less often humorous, within the framework of political discourse. Discourse in the context of this study is understood as a set of speech activities in the form of a dialogue or monologue, realizing a specific communicative goal under specific conditions or circumstances. During the description of the empirical material, the following components of the war discourse will be indicated: participants of the discourse, time and space, goals and strategies of action, values cultivated by the participants, which are the subject of reminiscence references, precedent texts and genre-specific linguistic units and constructions. The article consists of three parts. The first part contains the definition of an Internet meme, as well as the characteristics of this genre, including stylistic and media aspects. In the second part, I will present the structure of the war discourse, partly referring to the protest discourse. In the third part, I analyzed the empirical material, focusing on linguistic means and their historical, political and ideological characteristics. Material for the study was collected from February 2022 to June 2023 on Ukrainian websites, on YouTube, and on Telegram communicator blogs.